Effects of Engineered Type I Collagen on Hepatocyte Cultures - Lan, Cheng-Wen; Liu, Ting-Wei; Kuo, Shyh-Ming; Chang, Shwu-Jen (Current Nanoscience, 2011)
Primary hepatocytes in conventional mono-layer cultivation have been widely used as in vitro model for various studies. The major limitations of this model, however, are the rapid dedifferentiation and the reduction in liver-specific functions, such as cytochrome P450 (CYP) content, with increasing culture time. The reported studies indicated that the loss of the functional expression could be related to hepatocyte shape changes and the oxidative stress in the well-established hepatocyte isolation procedure with collagenase. Since hepatocytes' responsiveness to their extracellular matrix (ECM) is considered as an important role in the cellular fates of primary hepatocytes culture and Type I collagen is one of the most abundant ECM components in the liver tissue. In this study, two different engineered Type I collagen molecules, nano-sized collagen prepared by using high-voltage electrostatic field system and anti-oxidative collagen prepared by coupling α-lipoic acid, were applied to the hepatocytes cultured in suspension. The results demonstrated that the addition of nano-sized Type I collagen molecules with adequate concentration (5 x 10-4 mg/mL) could facilitate the cell aggregation and the formation of hepatic spheroids to approximately 5 mm in diameter after a 6-day culture in the stirring environment. The hepatocytes in spheroid were able to maintain an in vivo-like morphology and ECM materials secretion capability as seen in SEM observations. We also showed that the addition of anti-oxidative collagen molecules facilitated the maintenance of the gene expression of Cytochrome P450 (CYP3A) of hepatocytes up to 7-day culture. In summary, we have successfully demonstrated that the cell morphology and functional expression of primary cultured hepatocytes could be regulated by engineered collagen molecules as medium supplementation.
Keywords: Anti-oxidative